2019
DOI: 10.1177/1534734619880741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Far-Infrared Radiation Bioeffects on Micro Vascular Dysfunction, Nervous System, and Plantar Pressure in Diabetes Mellitus

Abstract: The most frequent clinical complication is diabetes. Diabetes is characterized by elevated blood glucose levels resulting in sensory nerve damage or lesions. Diabetic foot wounds are often slow to heal and require medical attention and monitoring. This study evaluates the effect of far-infrared radiation on the microcirculation and plantar pressure in the diabetic foot. Ten diabetics and 4 nondiabetics were recruited in this study. The diabetic group was examined before and after the intervention in each month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The increase in post-CT blood flow in the trapezius muscle could be derived from the decrease in sympathetic activity innervating the skeletal muscle microvasculature due to prolonged resting in the prone position. Another cause may be the continuous exposure to near-infrared light used in DCS measurement ( Ferraresi et al, 2012 ; Cheng et al, 2020 ). However, this contribution would be minor compared to that from MT.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in post-CT blood flow in the trapezius muscle could be derived from the decrease in sympathetic activity innervating the skeletal muscle microvasculature due to prolonged resting in the prone position. Another cause may be the continuous exposure to near-infrared light used in DCS measurement ( Ferraresi et al, 2012 ; Cheng et al, 2020 ). However, this contribution would be minor compared to that from MT.…”
Section: Discussionmentioning
confidence: 99%
“…Heating with infrared radiation has been used to treat microvascular dysfunction, sports injuries, etc. [ 25 , 42 ], which is generally more convenient to use, and is more suitable for detecting nerve and vascular function because of the instantaneous change in temperature and blood flow in the contralateral limb. The warm bath is widely used in the clinical and home therapy [ 22 ], and has a longer lasting thermal effect, and may be more suitable for use by people who suffer from skin lesions or wear an external fixator, and cannot accept the heat source being focused on one side of the limb.…”
Section: Discussionmentioning
confidence: 99%
“…There were also studies that demonstrated the microcirculation effects of FIR and thermal therapy on patients with diabetic foot and lymphedema, aiding in wound healing and microcirculation improvement. Cheng et al showed that FIR radiation would improve blood circulation with evidence of surface temperature and blood flow image improvement after 3 months of treatment [ 24 ]. Liu et al treated patients with lymphedema and lymphedematous skin by microwave and hot water immersion hyperthermia and showed near resolution of perivascular cellular infiltration, lymphatic lakes, and dilatation of blood capillaries [ 25 ].…”
Section: Discussionmentioning
confidence: 99%